2021
DOI: 10.21608/efmj.2022.80773.1075
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Bad News to Patients: Physicians’ awareness and Practice

Abstract: Background: Breaking bad news (BBN) is a routine yet distressing task for physicians and patients. Patients suffer considerable discomfort when bad news such as disease recurrence, spread or treatment failure is disclosed to them. Their physicians, therefore, should acquire effective communication skills to help them overcome these feelings. Objectives: To assess the physicians' awareness and practice of breaking bad news to patients. Methods: A crosssectional study was carried out in a rural Family Health Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
5
2
3
Order By: Relevance
“…The guidelines also are based on psychological aspects of which psychiatrists are most aware. This differs from the findings of other studies that found that family physicians and GPs have the highest scores [20,22] .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The guidelines also are based on psychological aspects of which psychiatrists are most aware. This differs from the findings of other studies that found that family physicians and GPs have the highest scores [20,22] .…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, the vast majority (91%) of physicians have a good agreement level and 8.6% had a partial agreement level with the principles of SPIKES protocol. This is similar to previous study done in Egypt [20] that found that more than two-thirds of the physicians had a good level of agreement and a qualitative study in Greece where all physicians agreed on the necessity to have principles for BBN similar to the SPIKES principles. In some studies, although physicians had appropriate awareness of the importance of BBN protocols, their practice was still unsatisfactory due to the absence of a consistent communication process and standardized procedures for BBN [21] .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations